The Literati and the Illuminati: Atlantic Knowledge Networks and Augustin Barruel’s Conspiracy Theories in the United States, 1794–1800 - Taylor, Jordan (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2019)
Augustin Barruel’s Memoirs Illustrating the History of Jacobinism incited the famous “Illuminati scare” in the United States from 1798 through 1800. Barruel argued that a shadowy Freemason group known as the Illuminati had provoked the French Revolution. Americans in the late 1790s inferred that this group was infiltrating the United States. Scholars often imagine that this scare was an instance of mass hysteria triggered by the intensity of American politics at this moment. But in fact, Americans’ response to Barruel was measured, careful, and guided by the era’s prevailing epistemological standards. Atlantic knowledge networks repeatedly validated (or failed to persuasively rebut) the content of the Memoirs, allowing American intellectuals such as Jedidiah Morse and Timothy Dwight to spread the conspiracy theory with the conviction of “authority.” Morse was particularly significant as a mediator between these networks and American audiences. By engaging with literary reviews, the correspondence of academics, and the publications of intellectuals, Morse had good reason to accept Barruel’s account. Indeed, the evidence that Morse and his allies marshalled in favor of Barruel was arguably stronger than that which was available to their critics. In this light, the Illuminati “scare” was not an irrational panic, but rather a reasonable response to the evidence available to Americans during the late 1790s. By re-examining this story through the lens of print history, transatlantic networks, and early modern processes of knowledge production, scholars can better understand the borders and limitations of early modern epistemologies, as well as the nature of early conspiracy theories.